Effectiveness of Impregnated Central Venous Catheters on Catheter-Related Bloodstream Infection in Pediatrics - Deng, Zhengrong; Qin, Jiangwei; Sun, Huanbin; Xv, Furong; Ma, Yimei (Frontiers in Pediatrics, 2022)
Background The efficacy and safety of impregnated central venous catheters (CVCs) in pediatrics remain controversial. The purpose of this study was to evaluate the efficacy of impregnations for the prevention of catheter-related bloodstream infection (CRBSI). Methods We searched the following five electronic databases: Medline, PubMed, Cochrane, Embase, and the Web of Science for randomized controlled trials (RCTs) up to March 2021. Pooled risk ratios (RRs) with 95% confidence intervals (CIs) were calculated using a fixed-effects model. Assessment of publication biases was evaluated by Egger's test. Heterogeneity between studies was assessed based on the chi-square test and I2 statistics, and sensitivity analysis and subgroup analysis were also performed. Results A total of six RCTs with 3,091 patients were included. Impregnated CVCs provided significant benefits in reducing the risk of CRBSI (RR = 0.41, 95% CI: 0.26–0.66) in pediatric patients, especially in the pediatric group. No publication bias was observed in the Egger test for the risk of CRBSI. Drug type is a source of heterogeneity. Conclusion Antimicrobial-impregnated CVCs are beneficial to prevent CVC-related complications in pediatrics.